The Promising Future for Complex Innovative Trial Design in Clinical Research - Sathian, Brijesh; van Teijlingen, Edwin; Banerjee, Indrajit; Asim, Mohammad; Kabir, Russell (Nepal Journal of Epidemiology, 2023)
Complex Innovative Trial Design (CID) offers several potential benefits for clinical research, including the use of novel statistical techniques such as adaptive designs and Bayesian methods that require computer simulation to determine operating characteristics. By leveraging these techniques, CID has the potential to increase the probability of success for clinical trials while simultaneously reducing the time and cost required for drug development.